Water resources and food security - Ringler, Claudia; Zhu, Tingju (Wiley, 2015)
Agricultural water use includes a continuum from purely rainfed to fully irrigated systems. Growing pressures on limited water supplies from domestic, industrial, and environmental uses will likely lead to a decline in water availability for food production. Similarly, income growth and urbanization lead to dietary shifts that require more water resources per calorie consumed, putting further pressures on water supplies. As a result, semiarid and arid countries continue to increase net imports of food. Crop water use for sugarcane (Saccharum officinarum L.), maize (Zea mays L.), soybean [Glycine max (L.) Merr.], and fruits are expected to grow over time, whereas water use for wheat (Triticum aestivum L.) and rice (Oryza sativa L.) are expected to decline after 2030. These projections include substantial improvements in water use efficiency at the field, farm, and river basin scale over the coming decades in response to growing water scarcity. If these efficiency improvements are not achieved, future crop water demands would be even larger. Although water resources are a key limiting factor for future food security, policy and investment options to reduce agricultural water use exist on both the water supply and demand side; but political will and ingenuity are needed for their implementation.